ANALISIS PEMBANGUNAN RENDAH KARBON STUDI KASUS PROPINSI LAMPUNG - Adi, Seno; aldrian, edvin; nuraini, dian; saroja, damayanti; tejakusuma, iwan G (Badan Pengkajian dan Penerapan Teknologi, 2011)
The increasing trend of CO2 emission globally, has been creating climate change in some areas in the world. The impact of climate change could cause disaster for human life such as drought and flood, health deseases, etc. Currently many programs and schemes are introduced to reduce CO2 emission. The low carbon development is one of those programs which is the economic development has to take into acount the CO2 emission reduction. This study found 90 % of the CO2 emision came from forestry sector, especially deforestation and fires. The recent CO2 emission was 70,3 MtCO2e in 2005 and estimated 79 MtCO2e in 2020, then finally will be 93,5 MtCO2e. Therefore mitigation actions should be focused on the forestry sector, these are reforestation & afforestation, REDD, mangrove rehabilitation, agroforestry development, and fire protection. These action programs potentially could reduce the CO2 emission as high as 76,8% in 2030.